SALAH PAHAM AL-MADAD DALAM AL-KUTÅªB AL-SITTAH: - Nur Raihan; Suliaman, Ishak (Department of Hadis Sciences (IH), Faculty of Usuluddin, Adab, and Da'wah (FUAD), State Islamic Institute of Langsa (IAIN), 2019)
The word Al-Madad in the Al-Kutub Al-Sittah is defined as help, that is, help given by Allah in the form of assistance from angels and help from living humans. However, the Habaib created a poem in the Qasidah